Digital Adaptive On-Time and Transient-Optimized Ripple Controlled Buck Converter - Pei-Jung Yang; Chun-Hsun Wu; Che-Yen Yeh; Le-Ren Chang-Chien (IEEE Access, 2023)
Ripple-based buck converters often encounter issues of operating frequency variation, system stability, and steady-state voltage error, leading to degradation in voltage regulation performance. While analog controls are commonly employed to address these issues, they still face challenges due to process uncertainty and component parameter drifting caused by chip aging. In contrast, digital controls are more able to immune to the challenges that analog circuits faced. However, the sampling rate and analog-to-digital conversion (ADC) are the two shortfalls that degrade circuit response time compared to that of the analog circuits. The weakness is being improved by design flexibility and algorithms. This paper introduces a novel approach utilizing a digital approach to reduce the variation of operating frequency to very low range, which is called digital constant frequency (DCF) control. Additionally, the digital transient-optimized control (DTOC) is proposed to significantly shorten the transient settling time. The digital control does not need to use the ADC. Given the load current change between 100 and 500mA, the DCF control reduced the operating frequency variation from 40% to 2.8%. Furthermore, the DTOC significantly shortened the settling time for both the rising and falling responses by 60% compared to the converter without DTOC.